FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PEMAKAIAN MASKER PADA PEKERJA KONTRAKTOR DI PACKING HOUSE P.10 PT INDOCEMENT TUNGGAL PRAKARSA Tbk KABUPATEN CIREBON - Hidayat, Fakih; Suryanto, Suryanto; Ulfah, Nur (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2013)
ABSTRACT Dust is one of the additional burden of the work environment as a result of chemical production processes. Based on data from NIOSH (Nationmal Institute for Occupational Safety and Health) in 2010 in the United States showed that mortality associated with occupational lung disease reached 70% of total deaths caused by work. Mask is one of the efforts to control the dusty work environment, to prevent occupational lung disease. However there are workers who do not wear masks at work. Many factors influence the behavior of workers that do not use the mask. The purpose of this study was to determine the factors associated with the behavior and the use of masks on contractors working in the packing house p.10 PT Indocement Tbk KabupatenCirebon. Type and method of this study is observational cross-sectional approach. Total sample of 52 respondents. Data were obtained through interviews with respondents using questionnaires and direct observation. The variables studied were the level of knowledge, level of education, perceptions, attitudes, age, years of employment, regulatory, and oversight by the clerk. Data analysis was performed by univariate and bivariate (chi square). The results showed that the variables significantly associated with the use of masks behavior is the level of knowledge (p = 0.021), regulation (p = 0.018) and oversight by the clerk (p = 0.038). While the variables are not significantly related to education level (p = 0.108), perception (p = 0.140), attitude (p = 0.120), age (p = 0.406), year (p = 0.184). Suggested activities necessary to the provision of information relating to the use of masks, and to improve the regulation and supervision of the frequency of use of masks to workers.   Keywords: Behavior, mask  Kesmasindo, Volume 6, ( 2), Juli 2013, Hal 125-134